Conceptualizing Convergence and Divergence Of Muslim Consumption Behaviour In Malaysia - Siti Hasnah, Hassan; Malliga, Marimuthu; Ernest Cyril, de Run (IJMS, 2013)
The Islamic culture is one of the largest and most unique cultures in the world and interest in Muslim related behaviour is increasing, although few marketers possess adequate knowledge and experience to interact appropriately with the various aggregate ethnic subgroups that make up the Muslim culture. Some new middle class Muslims are acutely aware of the dilemma of practising middle-classness in a contemporary lifestyle through the genuine and proper forms of consumption while also maintaining a religious identity that embodies piety. The consumption convergence or divergence represents the recognition of the changing nature of the world including the rapid developments in society brought about by economic development, urbanisation and access to the influences of other cultures through modernisation. This paper is a conceptual paper that proposes the idea of convergence and divergence of consumption behaviour and values. It hopes to give insight into the possible factors influencing the consumption trend and process of negotiating conflicting values of the modern middle-class Muslims as a means for a contemporary modern lifestyle. A conceptual framework outlining the factors affecting the cultural convergence and preference intention and consumption behaviour is proposed. Understanding the convergence and divergence issues in consumption is important to predict the potential market growth, segmentation, Islamic marketing and branding. The focus on the middle class and the policies for promoting it is rooted in the belief that the middle class is an important prerequisite for a stronger, more sustainable economic growth and development in the future.